2005
DOI: 10.1200/jco.2005.08.100
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine Plus Rituximab Is Effective and Has a Favorable Toxicity Profile in the Treatment of Mantle Cell and Low-Grade Non-Hodgkin's Lymphoma

Abstract: These results demonstrate that the BR combination is a highly active regimen in the treatment of low-grade lymphomas and mantle cell lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
258
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(273 citation statements)
references
References 16 publications
(1 reference statement)
11
258
1
3
Order By: Relevance
“…Additionally, recent data have suggested that bendamustine, either alone or in combination with rituximab, may be effective in patients with relapsed disease. 68 The consensus panel from the Fourth International Workshop on Waldenström's Macroglobulinemia also noted that autologous or allogeneic stem cell transplant should be considered in patients with high-risk disease. 11 High-dose therapy followed by autologous stem cell transplant has been performed in a growing number of patients with Waldenström macroglobulinemia.…”
Section: Treatment Of Relapsed Patientsmentioning
confidence: 99%
“…Additionally, recent data have suggested that bendamustine, either alone or in combination with rituximab, may be effective in patients with relapsed disease. 68 The consensus panel from the Fourth International Workshop on Waldenström's Macroglobulinemia also noted that autologous or allogeneic stem cell transplant should be considered in patients with high-risk disease. 11 High-dose therapy followed by autologous stem cell transplant has been performed in a growing number of patients with Waldenström macroglobulinemia.…”
Section: Treatment Of Relapsed Patientsmentioning
confidence: 99%
“…More promising data on the contrary have been recently achieved from the new combination of some 'old drugs' with rituximab, based on the results of the bendamustin-rituximab regimen (75% overall response rate, ORR -and 50% complete responses, CR -in relapsing disease) [16]. The impressive activity of bendamustin-rituximab has been also shown in first-line treatment [17], as well as the superior data of cytarabine in first-line young patients [6][7][8].…”
Section: Chemotherapy-based Approachesmentioning
confidence: 99%
“…Thalidomide and lenalidomide have shown modest activity in relapsed disease, suggesting possible enhanced activity in the frontline setting. [30][31][32] Rummel et al 33 reported on the activity of bendamustine combined with rituximab in relapsed lowgrade lymphoma and MCL. Only 16 patients enrolled on that study had MCL histology, but the overall response rate of 75% (CR 50%) in this subset supported studying this agent in randomized trials.…”
Section: New Chemotherapy Agentsmentioning
confidence: 99%